2015
DOI: 10.3899/jrheum.140474
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psoriatic Arthritis in a Large Cohort of Brazilian Patients with Psoriasis

Abstract: In our study, one-third of Brazilian patients with PsO, followed in dermatology settings, were diagnosed with PsA by a rheumatologist. Almost half of subjects with PsA had no previous diagnosis. A collaboration between dermatologists and rheumatologists is greatly needed to establish earlier PsA diagnoses and adequate multidisciplinary management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 28 publications
5
30
1
4
Order By: Relevance
“…This is consistent with the results reported in Ranza et al . (49.0%) that highlighted the frequency of undiagnosed cases. Some authors feel that the diagnosis of PsA should be facilitated by dermatologists, as underdiagnosis may lead to potentially avoidable joint damage that permanently disables and deforms some individuals …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is consistent with the results reported in Ranza et al . (49.0%) that highlighted the frequency of undiagnosed cases. Some authors feel that the diagnosis of PsA should be facilitated by dermatologists, as underdiagnosis may lead to potentially avoidable joint damage that permanently disables and deforms some individuals …”
Section: Discussionmentioning
confidence: 95%
“…This study demonstrated that the prevalence of PsA findings among Brazilian patients with PsO is in agreement with other investigations performed in Brazilian cohorts. Carneiro et al . and Ranza et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that many of the cases are first‐degree relatives, some of whom may be self‐reported. Patients with familial history of PsA developed psoriasis as well as inflammatory arthritis at an earlier age …”
Section: Discussionmentioning
confidence: 99%
“…По данным американских и евро-пейских исследователей [20,21], на долю больных ПсА приходится около 30% всех больных ПС. В бра-зильской популяции [22] ПсА отмечен у 33% паци-ентов с ПС. В азиатской популяции [23] распростра-ненность ПсА среди лиц с ПС значительно ниже -от 1 до 9%.…”
unclassified